Nothing like a duke - Ashford, Jane (Ashford, Jane. Duke's sons., 2017)
"Lord Robert Gresham has given up all hope that the beautiful and independent Flora Jennings will ever take him seriously. He heads to an exclusive country house party to forget about the beauty haunting his thoughts. When Flora shows up, Robert is nothing short of shocked. While Flora hates the expectations of fashionable society, she finds the annoyingly charming Lord Robert hard to resist. But while their attraction flares, someone much more sinister arrives and threatens Flora. Every fiber of Robert's being says to step in and save her...but some damsels in distress insist on saving themselves" -- provided by publisher.